2018
DOI: 10.1021/acs.molpharmaceut.8b00503
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thiolated PVP–Iodine Complexes: Key to Highly Mucoadhesive Antimicrobial Gels

Abstract: The aim of this study was to synthesize iodine containing polymeric excipients for mucosal treatment of microbial infection exhibiting a prolonged mucosal residence time by forming an adhesive gel on the mucosal surface. In order to achieve this aim, 2-(2 acryloylamino-ethyldisulfanyl)-nicotinic acid (ACENA) was copolymerized with N-vinylpyrrolidone (NVP) to obtain thiolated polyvinylpyrrolidone (PVP) for complexation with iodine. The average molecular mass of different thiolated PVP variants was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The use of PVP-iodine pre-treatment shown improved ability to prevent dental caries in vivo. Jalil et al demonstrated that the thiolated PVP and PVP-iodine complexes have shown significant mucosal adhesion for a prolonged duration of 3 h in comparison with the PVP and PVP-iodine complexes [ 168 ]. Hence, they reported that the thiol functionalized PVP is a promising novel excipient suitable for complexation with iodine to exhibit strong mucoadhesive properties.…”
Section: Pharmaceutical and Other Applicationsmentioning
confidence: 99%
“…The use of PVP-iodine pre-treatment shown improved ability to prevent dental caries in vivo. Jalil et al demonstrated that the thiolated PVP and PVP-iodine complexes have shown significant mucosal adhesion for a prolonged duration of 3 h in comparison with the PVP and PVP-iodine complexes [ 168 ]. Hence, they reported that the thiol functionalized PVP is a promising novel excipient suitable for complexation with iodine to exhibit strong mucoadhesive properties.…”
Section: Pharmaceutical and Other Applicationsmentioning
confidence: 99%
“…PVP is a nonionic polymer and lacks a high adhesion capacity to mucous membranes [99]. To improve the mucoadhesive properties of PVP and PVP-iodine, thiolated particles were synthesized via copolymerization of N-vinylpyrrolidone with 2-(2-acryloylethyldisulfanyl)nicotinic acid [89]. The resulting thiolated particles were well capable of producing gels with pig gastric mucin in higher-viscosity conditions.…”
Section: Applications Of Polymeric Iodophorsmentioning
confidence: 99%
“…Thiomers are a class of mucoadhesive materials which can be synthesised through the immobilisation of thiol groups on various materials. Some examples of thiomers include thiolated-polycarbophil [73], chitosan [74], pectin [75,76], graphene oxide [77], polyvinylpyrrolidone [78], and hyaluronic acid [79]. Their mucoadhesive properties can be due to their ability to form disulfide bonds with cysteine-rich domains of mucus glycoproteins via thiol/disulfide exchange reactions or oxidation of their thiol groups.…”
Section: Transmucosal Drug Deliverymentioning
confidence: 99%